Regeneration of a degraded ultisol with Tephrosia candida in the humid zone of southeastern Nigeria - Gichuru, M. (1994)
Continuous cropping in humid forest ecosystems results in soil fertility decline over time. The presence of appropriate tree or shrub species in the natural bush regrowth during a fallow can enhance recovery of soil fertility and shorten the fallow period required. Planted Tephrosia candida, a legume shrub known to nodulate well in acid soil, was compared with natural regrowth following 12 yr of continuous cropping with a single lime application (0, 0.5, 1.0, 2.0 and 4.0 t/ha) at the beginning of the cropping period. T. candida fallow improved both the physical and chemical properties of soil compared with natural regrowth alone. Maize yields were significantly increased in T. candida plots after a 2-yr fallow cycle; N and Ca uptake by maize was also improved. T. candida improved the nutrient content of maize grain and stover, and appeared to enhance nutrient cycling in addition to the N input through fixation.